Overview of Requirements Engineering Process for Software Product Lines - Snežana Šćepanović; Blažo Popović (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Software Product Lines is an important strategy to minimize costs and time-to market, and maximize quality and productivity of the software development. It involves the management of variabilities and commonalities among several applications, which increases its complexity compared to traditional software development. In this context, a Requirements Engineering and management are central tasks, important to reduce the risks involved in a development of product line. System requirements must be properly identified, analysed and reviewed in order to provide adequate solution to manage variabilities and integrating them for making easy the products derivation. In this paper Requirements Engineering process and techniques used in some of the product line practices are reviewed and discussed. Also, Requirements Engineering techniques for traditional single product software development are analysed and their applicability in product line development is assessed.
Keywords: C88; L86; 330; requirements engineering; software product lines; innovation; technology